2020
DOI: 10.1038/s41416-020-01039-5
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy as a therapeutic target in pancreatic cancer

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is characterised by early metastasis and resistance to anti-cancer therapy, leading to an overall poor prognosis. Despite continued research efforts, no targeted therapy has yet shown meaningful efficacy in PDAC; mutations in the oncogene KRAS and the tumour suppressor TP53, which are the most common genomic alterations in PDAC, have so far shown poor clinical actionability. Autophagy, a conserved process allowing cells to recycle altered or unused organelles and cellula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
94
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(106 citation statements)
references
References 124 publications
(181 reference statements)
3
94
0
Order By: Relevance
“…In addition, we previously reported that lab-generated MAL3-101 resistant rhabdomyosarcoma cells, which were obtained by long-term dose escalation, could be partially resensitized to MAL3-101 if autophagy was simultaneously inhibited (Sannino et al, 2018). Together, our study supports the importance of monitoring autophagy efficiency in various cancers in parallel to the development of specific autophagy inhibitors that can be administrated alone or in combination with approved secondary therapies (Amaravadi et al, 2011;Chude and Amaravadi, 2017;Piffoux et al, 2020;Rebecca et al, 2019;Shi et al, 2017).…”
Section: Discussionsupporting
confidence: 75%
“…In addition, we previously reported that lab-generated MAL3-101 resistant rhabdomyosarcoma cells, which were obtained by long-term dose escalation, could be partially resensitized to MAL3-101 if autophagy was simultaneously inhibited (Sannino et al, 2018). Together, our study supports the importance of monitoring autophagy efficiency in various cancers in parallel to the development of specific autophagy inhibitors that can be administrated alone or in combination with approved secondary therapies (Amaravadi et al, 2011;Chude and Amaravadi, 2017;Piffoux et al, 2020;Rebecca et al, 2019;Shi et al, 2017).…”
Section: Discussionsupporting
confidence: 75%
“…Although the role of autophagy seems to be tumour-suppressive in the initial stages of cancer, the hyper-active autophagy-dependent self-cannibalism has serious negative effects in tumour progression in the later stages. Therefore, the downregulation of autophagy by using various drugs (i.e., chloroquine or hydroxychloroquine) might have an important role in cellular survival [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…PC is a solid tumor with a highly malignant behavior, which has become the fourth largest cancer causing cancer-related death in western countries, with a 5 years survival rate of less than 10% (Siegel et al, 2019). Accumulated evidence showed that autophagy got involved in tumor development and treatment resistance in PC (Piffoux et al, 2020). Thus, it is essential to screen autophagy-related molecular to identify effective prognostic biomarkers for PC.…”
Section: Discussionmentioning
confidence: 99%